Strategi Kepala Sekolah dalam Mengembangkan Sistem Pendidikan Menuju Madrasah Unggul di MI Islamiyah IV Pragaan Daya - Fathorrahman Fathorrahman; Nurul Aini (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
This article examines the strategies employed by school principals in developing an education system towards excellence in MI Islamiyah IV Pragaan Daya. It describes the principal's strategies and explores the supporting and inhibiting factors that influence the implementation of these strategies. The study adopts a qualitative research approach, specifically a case study method, utilizing observation, interviews, and data collection techniques. To ensure data validity, measures such as credibility, transferability, dependability, and confirmation are employed. The research findings indicate that the principal's strategies include enhancing teacher capacity, utilizing educational media and tools, fostering community collaboration, and enforcing discipline. These strategies encompass various aspects such as non-academic achievements, extracurricular activities, outputs, and the development of educational components such as goals, teachers and staff, curriculum, forecasting, and environment. However, several inhibiting factors are identified, including low student motivation, discipline issues, and limited financial resources. On the other hand, supporting factors include education, forecasting, and human resources.